2004
DOI: 10.3171/jns.2004.100.4.0597
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery for idiopathic trigeminal neuralgia performed using a far-anterior cisternal target and a high dose of radiation

Abstract: To optimize pain control and minimize complications of this therapy, we recommend that the nerve be targeted at a distance of 5 to 8 mm from the brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
107
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 22 publications
9
107
1
1
Order By: Relevance
“…Our excellent and good outcome rates are comparable to those reported in previously published studies. 6,8,17,19,23 The observed excellent and good outcome rates in our patients as well as those of other large studies published in the last decade are summarized in Table 2.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Our excellent and good outcome rates are comparable to those reported in previously published studies. 6,8,17,19,23 The observed excellent and good outcome rates in our patients as well as those of other large studies published in the last decade are summarized in Table 2.…”
Section: Discussionsupporting
confidence: 74%
“…8,16 Numerous authors have reported on SRS with the GK, and outcome and complication rates have been variable. [1][2][3][4][5][6]8,[10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The observed variation in success rates in the literature may be explained by the subjectivity of assessing pain (which is the most important outcome parameter in these studies), the multifactorial causes of TN (idiopathic or secondary to a pathological entity), the significantly varying stereotactic radiosurgical treatment protocols (different anatomical targets and different radiation doses), and the usage of illdefined and widely variable outcome assessment criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations